The 28 November 2020 landslide, tsunami, and outburst flood – a hazard cascade associated with rapid deglaciation at Elliot Creek, British Columbia, Canada - Geertsema, Marten; Menounos, Brian; Bullard, G.; Carrivick, Jonathan L.; Clague, J. J.; Dai, Chunli; Donati, Davide; Ekstrom, Goran; Jackson, Jennifer M.; Lynett, Patrick; Pichierri, M.; Pon, Andy; et al. (American Geophysical Union (AGU), 2022)
We describe and model the evolution of a recent landslide, tsunami, outburst flood, and sediment plume in the southern Coast Mountains, British Columbia, Canada. On November 28, 2020, about 18 million m3 of rock descended 1,000 m from a steep valley wall and traveled across the toe of a glacier before entering a 0.6 km2 glacier lake and producing >100-m high run-up. Water overtopped the lake outlet and scoured a 10-km long channel before depositing debris on a 2-km2 fan below the lake outlet. Floodwater, organic debris, and fine sediment entered a fjord where it produced a 60+km long sediment plume and altered turbidity, water temperature, and water chemistry for weeks. The outburst flood destroyed forest and salmon spawning habitat. Physically based models of the landslide, tsunami, and flood provide real-time simulations of the event and can improve understanding of similar hazard cascades and the risk they pose.
Keywords: landslide; hazard; cascade; deglaciation; glacial lake; tsunami; outburst flood